(3JaSjQ GdbQBf GdcQjes - (3LeGd GdOjf eMeO Hf Ydj GdGYbes ((3CMeO Hf SYO Hf YWjI GdTGei s)
(3ChdgG (B:s
(3GdMeO ddg GdPi fRd GdaQbGf Ydi bdH fHjg GdeNJGQ , aLYdg YR hYdG ef CYXe GdMLL GdgGFdI hGdBjGJ GdHGgQI s
(3BNQgG (B:s
(3jfJgi HBNQ ShQI Gdcga , hBNQ eG ajg (B: (3hEf cGf eVLYg HecI cGf dg fhQkG HJdC dC ef eVLYg Edi GdHjJ GdeYehQ MJi jSJjbX s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG JYdjbGJ hEVGaGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3JaSjQ (B63) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs